PERAN STRATEGIS KELAS MENENGAH DALAM PILKADA - Utomo, Setyo (UIR PRESS, 2017)
In note of history of existence of middle-weight in society often influence process of political and social change, either in in and also beyond the sea. History of French revolution which is in marking with existence of Industrial revolution mark change of social that happened at society of Europe which is in motorizing by middle-weight. History in Indonesia also show position of middle clan take possession of central position in menetukan process social change in the middle of society, start independence era, transition from old order to new order till the happening of reform 98 which is in motorizing by middle-weight that is elite figure and mahasiswa.Dalam of context of pilkada of middle-weight in Indonesia also always become determinant in colouring process of execution of regional leader election, either through quality of execution democratize in storey;level local ( pilkada) and also in influencing society of elector to take choice its in chosening leader of governance in area